Business Model Scenarios for Remote Management - Olivier Braet (Journal of Theoretical and Applied Electronic Commerce Research, 2007)
This article critically appraises business model challenges in implementing remote managementfunctionalities. Remote management is believed to create new service opportunities and foster convergencebetween previously dissociated islands of end user devices. Conflicting business logics from disparateindustries, however, run counter to this attempt at centralization. We introduce a generic business modelingmethodology that aims to move beyond traditional ICT investment appraisal techniques by combining fourcritical dimensions of design. We develop four business model scenarios based on the organizational designchoice of ´degree of vertical integration´ and the product design choices of ´degree of product modularity´ and´distribution of intelligence´ and offer a description of the effect of these design choices on the intendedcustomer value.